2018
DOI: 10.1155/2018/5702646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Afternoon Nap Deprivation on Adult Habitual Nappers’ Inhibition Functions

Abstract: Multiple studies have established the effects of afternoon naps on cognition. However, relatively few studies have investigated the domain of executive functions. Moreover, the effects of napping on inhibition are far from conclusive. The present study employed adult habitual nappers to investigate the effects of afternoon nap deprivation on response-based inhibition assessed by a Go/No-go task and stimulus-based inhibition assessed by a Flanker task and on alertness assessed by a psychomotor vigilance test (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Regarding the relatively complex executive function of response inhibition, the current study found that accuracy on the GNG task increased significantly with an afternoon nap, regardless of test session. These findings were partly consistent with some studies (Chen et al., 2018; Ru, Chen et al., 2019). For example, Chen et al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding the relatively complex executive function of response inhibition, the current study found that accuracy on the GNG task increased significantly with an afternoon nap, regardless of test session. These findings were partly consistent with some studies (Chen et al., 2018; Ru, Chen et al., 2019). For example, Chen et al.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Chen et al. (2018) found that a midday nap significantly improved accuracy and reaction speed on the GNG task but did not affect the flanker task performance. Although the GNG and flanker tasks are typical tasks assessing inhibition control, they stress action inhibition and attention inhibition, respectively (Diamond, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daytime nap deprivation is considered sleep loss, particularly for people who are habitual nappers, as daytime naps are frequently included in their total sleep time. in China, most people prefer a brief nap at midday or early afternoon as a practical option to alleviate the post-lunch dip or compensate for insufficient sleep at night ( 17 ). In total, 38.91% of Chinese students nap, with 65% of them napping at least once a week ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%